Edukasi dan Pemeriksaan IMT (Indeks Masa Tubuh) pada Pondok Pesantren Madinatul Munawarah Kota Bukittinggi - Renatalia Fika; Mevy Trisna; Budi Setiawan; Yonrizon Yonrizon; Muhajri Agusfina; Mia Arifka (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
This Community Service is entitled Education and Examination of BMI (Body Mass Index) at the Madinatul Munawarah Islamic Boarding School in Bukittinggi City. Body Mass Index is defined as a person's weight in kilograms divided by height in meters. The purpose of this PKM is to increase awareness and knowledge of students in paying attention to their health regarding BMI, as well as providing education on effective prevention and management methods in maintaining ideal weight and height. This PKM is carried out through health counseling, health checks, and education about healthy lifestyles. The students targeted in this study are from the Madinatul Munawarah Islamic Boarding School in Bukittinggi City. Before the counseling, 26 students were given counseling about their knowledge of BMI / Body Mass Index. Then after the counseling, a health check was also carried out through measuring height and weight. The BMI of the students turned out to show BMI figures that could be categorized as follows: the highest normal category of BMI measurement was 14 people out of 26 participants (54%), and followed by the thin category of 7 people out of 26 participants (27%) while the obese were 5 people out of 26 participants (19%) from the results of calculations using the formula. After counseling and health checks, the students targeted in this study were from the Madinatul Munawarah Islamic Boarding School in Bukittinggi City showed an increase in awareness and knowledge about BMI. Most participants also showed changes in a healthier lifestyle, such as increasing consumption of fruits and vegetables, and doing physical activity regularly. This PKM shows that health education and counseling can increase awareness and knowledge of the students targeted in this study were from the Madinatul Munawarah Islamic Boarding School about BMI. Thus, the students targeted in this community service from the Madinatul Munawarah Islamic Boarding School in Bukittinggi City, can carry out effective prevention and management to reduce the risk of overweight disease.